The Post-PARC Interface and the Visualization of Documents and of their Relationships - Vaillancourt, Alain; Marcoux, Yves (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
We propose an evolution path for the traditional "PARC" interface found today on most PCs. The proposal, which we call the "post-PARC interface", draws not only on concepts developed at major research laboratories like PARC and HCIL, but also on the work of independent researchers. It is based on two novel concepts: the representation of documents by visual objects that evolve. . .